Study on the Anode Materials of Mn-Co3O4 for Lithium Ion Secondary Batteries - Yin, Lihui (Asian Journal of Chemistry, 2012)
The anode materials of Co3O4 for lithium-ion batteries are made by adding certain amount of manganese powder to Co3O4 and ball milling. Electrochemical properties of Co3O4 and Mn-Co3O4 powders are tested, respectively and the results are as follows: when the Co3O4 powder is independently used as the anode of lithium-ion batteries, the first charge and discharge efficiency is as low as 66 % with bad cycle performance; when Mn powder is added, the first charge and discharge efficiency is improved to 77 % with good cycle performance, the reversible capacity is still kept at 702 mAh g-1 after 50 cycles and the coulomb efficiency is over 97 %.